The influence of plastic zone area on the general deformation of T-girder - Bela, Sabo; Alanović, Jadranko (Journal of Production Engineering, 1990)
This article presents the results of an investigation into the influence of the plastic zone area on the overall deformation of a welded T-girder. The plastic zone area was determined through the analysis of macro-sections and compared to calculated values using N.O. Okernom. Based on the experimental findings, two relationships were examined: one between the actual and calculated values of the plastic zone area and another between the curvature of the elastic line and the actual values of the plastic zone area. The welding process utilized manual metal arc welding (MMA) with varying heat input levels. Covered electrodes with different diameters (2.5 mm, 3.25 mm, 4.0 mm, and 5.0 mm) were employed. Throughout the welding process, measurements were taken for welding current, arc voltage, and active welding time. Additionally, the deflection of the girder after the welding process was recorded. Following welding, specimens were cut out for macro-section analysis. Measured and calculated values are presented in tables and graphically. Building on the aforementioned relationships, an equation for determining the curvature of the elastic line, dependent on the calculated plastic zone area, was derived.